Фізичне моделювання однофазного резонансного напівпровідникового перетворювача з фазовим способом керування - Лобко, Андрій Валерійович (НТУ "ХПІ", 2016)
Метою статті є аналіз можливостей забезпечення режиму м’якої комутації на основній частоті 50 Гц в однофазному резонансному перетворювачі з фазовим способом керування за результатами фізичного моделювання зазначеного перетворювача. Розглянуто напівпровідниковий резонансний перетворювач з фазовим способом керування, розроблено методика розрахунку основних параметрів перетворювача, а також побудовано алгоритм роботи мікропроцесорної системи керування. Для підтвердження отриманих результатів використано комп’ютерне та фізичне моделювання перетворювача.

The article is devoted to the development of energy-efficient converter for advanced power systems. The main goal is to analyze the possibilities of providing the soft switching mode at the fundamental frequency of 50 Hz in single-phase resonant converter with phase control method using physical modeling results of converter which was mentioned. The major attention is paid to principles of phase control of single-phase resonant converter, the development of a methodology of calculation of the main parameters of the converter, its structure and the control algorithm for the microprocessor-based control system, which provides a soft switching mode using the principles of phase control method. The algorithm of microprocessor control systems of single-phase resonant converter that implements phase control method is discussed. The vector diagrams that explained the principle of determining the angle control necessary for automatic voltage regulation system at load are presented. It is shown that developed phase control method allowed to create a method by which were obtained analytical expressions, based on which have been calculated main parameters of single-phase resonant converter with phase control method. Block diagram of the converter, main blocks description and the relationship between them are presented. The results of computer simulation and verification of their adequacy using a physical model of the converter were performed. The conclusions about the possibilities of providing the soft switching mode at the fundamental frequency of 50 Hz in converter with phase control method in various modes are suggested. These conclusions are supported by the experimental data.
Physical simulation of resonant single-phase semiconductor converters with phase operating methods
Keywords: комп’ютерне моделювання; векторна діаграма; алгоритм; мікропроцесорна система керування; computer modeling; vector diagram; algorithm; microprocessor control system